The cytochrome P450 CYP389C16 contributes to the cross‐resistance between cyflumetofen and pyridaben in Tetranychus cinnabarinus (Boisduval). Issue 2 (26th August 2019) - Feng, Kaiyang; Ou, Shiyuan; Zhang, Ping; Wen, Xiang; Shi, Li; Yang, Yuwei; Hu, Yuan; Zhang, Yichao; Shen, Guangmao; Xu, Zhifeng; He, Lin
Abstract: BACKGROUND: Acaricide resistance is a serious problem in spider mites. Cyflumetofen is a new complex II inhibitor, whereas pyridaben acts at complex I and has been used for decades. Although cross‐resistance between cyflumetofen and pyridaben has been observed in Tetranychus cinnabarinus, the specific mechanisms at play have not yet been investigated. RESULTS: Investigation into the cross‐resistance mechanisms identified five P450s, among which CYP389C16 was evaluated as the most likely candidate conferring cross‐resistance. Knockdown of CYP389C16 expression via RNA interference diminished the level of cross‐resistance in the cyflumetofen‐resistant strain. In addition, recombinant CYP389C16 (40 pmol) effectively metabolized 25.0 ± 0.7% of cyflumetofen, 39.7 ± 1.0% of pyridaben, and 69.3 ± 3.3% of AB‐1 (active de‐esterified metabolite of cyflumetofen) within 2 h. In addition, hydroxylation metabolite of AB‐1 was identified by HPLC‐MS/MS. CONCLUSIONS: The study reveals that overexpressed CYP389C16 is involved in the cross‐resistance between cyflumetofen and pyridaben in T. cinnabarinus . © 2019 Society of Chemical Industry Abstract : CYP389C16 contributes to the cross‐resistance between cyflumetofen and pyridaben in Tetranychus cinnabarinus .